What Would Steve Jobs Do? How the Steve Jobs Way Can Inspire Anyone to Think Differently and Win (Audio Book) - Sander, Peter (McGraw-Hill, 2011)
Lead and Succeed Like the World's Greatest Business Innovator There's no accounting for Steve Jobs's mind. He just didn't think the way the rest of the world does. Regarded by many as the most innovative and influential business leader of our time, Jobs was a visionary beyond compare. He was why Apple is Apple and everyone else is everyone else. We can't transform ourselves into Steve Jobs. How he put his ideas into action, however, was systematic, efficient, focused, and smart. And this you can do. What Would Steve Jobs Do? presents the six-part business model Jobs applied to make Apple the most valuable publicly traded manufacturing corporation in the world and the global model for business excellence. While the results of this model can be profound, each step is something you can easily focus on with clarity and purpose: Customer -Understand your customers so well that you know what they want more than they do. Vision -Don't stop thinking at "new product"; synthesize your ideas, products, and technologies around a specific game-changing customer issue. Culture -Create an environment filled with people who consider "can't" a bad word. Product -Approach your product as something that can change the world- not just something to beat the competition or get a job done. Message -Deliver a message so compelling that it becomes an extension of the product itself. Personal Brand -Make people think constancy, promise, and trust when they think of you. Steve Jobs was a true original. What we've all learned from him is incalculable. And what we can continue to learn from him will shape the world. Transform your organization, recast your future, and do your part to redefine our world using the wisdom and foresight of the greatest business sage in generations.